Enhancing the flexural strength of green high performance concrete beams by carbon fiber reinforcement - Mohammed Najat Ahmed (Genius Journals, 2022)
An experimental work was carried out to investigate the flexural strength of Green High Performance Concrete (GHPC) beams reinforced with carbon fibers with volume fractions 0.3%,0.6%,and 1%. For this, GHPC mixtures were produced using silica fume (SF) at 20 percent as a partial substitute by cement weight, in addition to using the super plasticizer (SP) to obtain the appropriate workability with low w/b ratio. A constant w/b ratio of 0.35 was used for the produced mixtures, and in order to control the workability of the mixtures, the super plasticizer ratios were modified. Standard curing was used in this study, then the beam specimens were tested for flexural strength. The addition of fibers to non-fibrous GHPC beams changed the non-fibrous matrix's brittle behavior to ductile behavior. The results show that carbon fibers improves beams flexural strength considerably.The beams reinforced with carbon fiber with fractions of volume of 0.6 % , demonstrated the highest flexural strength.
Keywords: Flexural Strength; Green High Performance Concrete,; Silica fume; Carbon Fiber